Role of Fenugreek, Cinnamon, Curcuma longa, Berberine and Momordica charantia in Type 2 Diabetes Mellitus Treatment: A Review - Marisol Cortez-Navarrete; Karina G. Pérez-Rubio; Miriam de J. Escobedo-Gutiérrez (MDPI AG, 2023)
Type 2 diabetes mellitus (T2DM) is a complex disease that has become a major global health concern. Given the efficacy of antidiabetic drugs, pharmacological therapy is considered the first-line treatment of T2DM; however, due to their potential side effects and high costs, new and cost-effective treatments with minimal side effects are needed. Medicinal plants have been used for centuries as part of traditional medicine to treat T2DM. Among these, fenugreek, cinnamon, Curcuma longa, berberine, and Momordica charantia have demonstrated different degrees of hypoglycemic activity in clinical studies and animal models. Therefore, the aim of this review is to synthesize the mechanisms of action of five medicinal plants, as well as the experimental and clinical evidence of their hypoglycemic activity from the published literature.